2014
DOI: 10.1080/00224499.2014.953023
|View full text |Cite
|
Sign up to set email alerts
|

Condoms and Contexts: Profiles of Sexual Risk and Safety Among Young Heterosexually Active Men

Abstract: Heterosexual men’s sexual safety behavior is important to controlling the U.S. epidemic of sexually transmitted infections (STIs), including HIV. While sexual safety is often treated as a single behavior, such as condom use, it can also be conceptualized as resulting from multiple factors. Doing so can help us achieve more nuanced understandings of sexual risk and safety within partner-related contexts. We used Latent Class Analysis with data collected online from 18-25 year old heterosexually active U.S. men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
2
6
0
1
Order By: Relevance
“…The results yielded three distinctive sexual risk–safety profiles: birth control in a relationship (sexual health discussion, contraceptive use in a long-term stable relationship), condom users (consistent condom use, with regular partners), and risk-takers (sexual risk-taking behavior related to HIV transmission, unintended pregnancy, and multiple sexual partnerships). These findings are congruent with previous studies on adolescents and men (Beadnell et al, 2005; Masters et al, 2015). The cluster analysis approach provides an advantage over more traditional statistical techniques by identifying distinct sexual safety profiles that might best benefit from interventions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results yielded three distinctive sexual risk–safety profiles: birth control in a relationship (sexual health discussion, contraceptive use in a long-term stable relationship), condom users (consistent condom use, with regular partners), and risk-takers (sexual risk-taking behavior related to HIV transmission, unintended pregnancy, and multiple sexual partnerships). These findings are congruent with previous studies on adolescents and men (Beadnell et al, 2005; Masters et al, 2015). The cluster analysis approach provides an advantage over more traditional statistical techniques by identifying distinct sexual safety profiles that might best benefit from interventions.…”
Section: Discussionsupporting
confidence: 93%
“…Although the need to explore diverse sexual behaviors jointly, in a holistic, multidimensional way has been highlighted (Tolman & McClelland, 2011; Vasilenko et al, 2014; Wesche, Lefkowitz, & Vasilenko, 2017), person-oriented studies about sexual risk–safety behaviors remain relatively limited. A few have examined patterns of sexual relationships (Espinosa-Hernàndez & Vasilenko, 2015; Haydon, Herring, Prinstein, & Halpern, 2012; Lanza & Collins, 2008; Vasilenko, Kugler, & Lanza, 2016) or of sexual risk behaviors among young people (Beadnell et al, 2005; Hipwell, Stepp, Keenan, Chung, & Loeber, 2011; Masters et al, 2015; Vasilenko, Kugler, Butera, & Lanza, 2015; Wesche et al, 2017). Most of these were based on key variables such as condom use, number of partners, and frequency of sex and found three to five different sexual profiles (e.g., low-risk youth, high-risk youth, monogamy strategy, condom strategy; Newman & Zimmerman, 2000), identifying relatively healthy to risky patterns of sexual behavior among adolescents.…”
mentioning
confidence: 99%
“…It suggests the need for conceptually distinguishing between sexual behavior driven by callous misogyny, and non-coercive sexuality that is focused on variety and experience seeking. Indeed, in a separate examination of the sexual scripts of men in this sample (their ideas about how sex and relationships “should be”), we found that many men endorsed a sexuality not tied to romantic intimacy, but at the same time placed an emphasis on positive, mutual, consensual experiences for both themselves and their female partners (Masters et al, 2015). Thus, it may be important to more specifically elicit the sex-related cognitions or perceptions of cultural sexual norms related to an impersonal approach to sex which is inclusive of coercion, versus those associated with a mutually respectful, sex-positive approach that endorses non-monogamy and multiple partners over time.…”
Section: Discussionmentioning
confidence: 96%
“…The alternative is also plausible, where HIV testing and condom use are common among men in monogamous relationships, or even men with multiple partners, not only in order to prevent HIV but also to prevent other sexually transmitted infections or unwanted pregnancy. Other studies have also reported that men who use condoms consistently were more likely to get tested than those who do not (Masters et al, 2014). Further research is needed to investigate condom use and HIV testing in Haiti, paying close attention to correlates of HIV testing and consistency of condom use among men.…”
Section: Discussionmentioning
confidence: 99%